Дослідження алгоритмів продуктивності різних платформ розважального контенту - Гриценко, І. О. (ХНУРЕ, 2025)
This work is devoted to analysis of the algorithms of different video platforms such as YouTube, Netflix and TikTok. The basic work methods of the platforms and view of pros and cons.
Keywords: розважальний контент; video platforms